Efectivity of Participatory Institution in Citarum River Upstream Watershed - Halimatusadiah, Siti; Hadi Dharmawan, Arya; r, Rin (Sodality: Jurnal Sosiologi Pedesaan, 2012)
Upstream watershed is one of the sub-watersheds that serve to maintain the availability of water for the central and downstream region. So that, when damage occurs in that area, it will effect to the middle and lower area of the watershed. The purposes         of this study were (1) to determine the stakeholders who involved in the rescue of Citarum watershed upstream, (2) to know the effectiveness of participatory institutions to change attitudes and behavior of society around the Citarum watershed upstream. This study was conducted using a quantitative approach supported by qualitative approach. Meanwhile, the results of this study showed (1) institutional participatory have successfully changed   attitudes and behavior of society to not to dispose the household garbage and sewage into the river again (2) participatory institutional not yet managed to change the manner of private parties to not  to dispose garbage and industrial waste into the river, and (3) participatory institutions in central  are more effective to change society attitudes and behavior to be more concerned for the environment than the existing participatory institutions in the upstream. In generally, the participatory institutions have successfully established collaborative between public, private and government at the sub-watershed upstream.